(untitled) (Progressive Agriculture, 2013)
G-50 chromatography of extract of paddy plant induced by urea revealed the major three peaks F-1, F-2 and F-3 against the absorbance at 280 nm with the number of fractions. Chromatogram was also obtained from the control of extract of paddy, however, urea-induced paddy extract showed the higher absorbance than the control showing the higher protein content. F-1 fraction for both groups having the higher molecules are considered to have the urea transporter and are applied to SDS-PAGE for purification and characterization. For identification of urea transporter, a mixture of marker proteins- ?-galactosidase, BSA, egg white albumin, pepsin, trypsin inhibitor and lysozyme were used. Depending on the mobility of the sample, urea-transporter had been identified as a large band having the MW of 50.6 kDa compared to the MW of BSA. For control, SDS-PAGE shows the same band for urea-transporter but the expression was lower than the urea-treated paddy. In SDS-PAGE gel, both bands were homogenous showing the homogeneity of urea-transporter. The results demonstrate that urea application in the soil induces the expression of urea transporter which will be a new finding for the clarification of mechanism of urea transport in plants. DOI: http://dx.doi.org/10.3329/pa.v18i2.17463 Progress. Agric. 18(2): 41 - 47, 2007